2021
DOI: 10.1177/17455065211002488
|View full text |Cite
|
Sign up to set email alerts
|

“I never heard anything about it”: Knowledge and psychosocial needs of Latina breast cancer survivors with lymphedema

Abstract: Objective: Breast cancer is the most commonly diagnosed form of cancer and the leading cause of cancer-related death among Latina women in the United States. One aspect of recovery that has been underrepresented in the English-language literature is the recovery of Latina women who have developed lymphedema, a debilitating condition characterized by persistent swelling of the arm, hand, chest, and/or breast. To fill this research gap, a study was conducted to examine the lived experiences of Latina women with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The physical and financial burdens of lymphedema often lead to psychological sequelae including concerns about body image and constant reminders of their breast cancer diagnoses and treatments 39 . Moreover, individuals from minoritized and marginalized groups with lymphedema report even worse outcomes related to mental and physical health and quality of life 40 . Financial repercussions are often greater in those populations given their disproportionate representation in occupations requiring manual labor with less generous flexibility and benefits 40 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The physical and financial burdens of lymphedema often lead to psychological sequelae including concerns about body image and constant reminders of their breast cancer diagnoses and treatments 39 . Moreover, individuals from minoritized and marginalized groups with lymphedema report even worse outcomes related to mental and physical health and quality of life 40 . Financial repercussions are often greater in those populations given their disproportionate representation in occupations requiring manual labor with less generous flexibility and benefits 40 .…”
Section: Discussionmentioning
confidence: 99%
“…39 Moreover, individuals from minoritized and marginalized groups with lymphedema report even worse outcomes related to mental and physical health and quality of life. 40 Financial repercussions are often greater in those populations given their disproportionate representation in occupations requiring manual labor with less generous flexibility and benefits. 40 Combined with higher monthly costs, marginalized and minoritized individuals are placed at an undue burden of economic disadvantage.…”
Section: Low Value Surgical Carementioning
confidence: 99%
See 1 more Smart Citation
“…Spiritual/existential needs Overall, there were twelve studies where spiritual needs were reported by breast cancer survivors [50,51,46,42,40,33,30,27,12,4]. Religion and/or spirituality were an important source of emotional support for them [42,45,46].…”
Section: Social Needsmentioning
confidence: 99%
“…Further, they have reported receiving critical information in support groups such as details about treatments, where to purchase breast prostheses, and the process of reconstructive surgery (Buki, Schwartz, et al, 2021; Galván et al, 2009). Instrumental support, which includes financial assistance and help with household chores, has also helped Latina survivors manage their condition (Ashing-Giwa et al, 2006; Buki, Rivera-Ramos, et al, 2021; Galván et al, 2009). Research is lacking, however, on the experiences of women diagnosed twice and how a previous experience with cancer manifests as they cope with a second diagnosis.…”
Section: Latina Women’s Experiences With a First Breast Cancer Diagnosismentioning
confidence: 99%